Evaluation of the feasibility of intrapancreatic delivery of drug-loaded microparticles via EUS-guided fine needle injection using a swine model - Caceres, Jennifer; Munoz-Sagastibelza, Maria; Hossian, A. K. M. Nawshad; Paredes, Jenny; Barrera, Kaylene; Mattheolabakis, George; Martello, Laura A.; Vignesh, Shivakumar (Endoscopy International Open, 2019)
Background and study aims Patients with pancreatic cancer often have locally advanced or metastatic disease and are not candidates for curative surgery. Polymer-based microparticles (MPs) represent a drug delivery system that offers sustained release of a chemotherapeutic drug after intralesional injection for local tumor management. The aim of this study was to determine the feasibility of endoscopic ultrasound-guided fine-needle injection (EUS-FNI) of drug-loaded MPs tagged with a fluorophore and fiducial markers for locating the injection site. Secondary aims were to determine the tissue-specific effects of MPs.Methods Five pigs underwent EUS with selection of an injection site within the pancreas that was marked by placing fiducial markers prior to the MPs injection. EUS-FNI of either blank microparticles (BMPs), containing no drug, or gemcitabine-loaded microparticles (GMPs) was performed. A saline flush containing Spot Endoscopic Marker was used to expel any residual MPs in the needle shaft and tattoo the injection site. Results A green fluorescent protein flashlight was used to successfully identify the site of MP injection sites in the dissected pancreas. Frozen sections of pig pancreas demonstrated a defined deposit, confirming the delivery of the MPs. Finally, fluorescence microscopy showed activation of caspase-mediated cell death in pancreases of animals that received injections of GMPs.Conclusions This pilot study demonstrated that fiducial marker placement and pancreatic EUS-FNI of MPs was successful in all pigs with no animals demonstrating pancreatitis. Further studies are needed to determine the role for intralesional injection of drug-loaded MPs in borderline resectable or unresectable pancreatic cancer.